Abiding by the law when it does not exist: The case of the helmet bicycle law. (July 2020) - Valero-Mora, Pedro M.; Shinar, David; Ledesma, Rubén D.; Tormo Lancero, María Teresa; Sánchez-García, Mar; Haworth, Narelle; Sanmartín, Jaime; Morandi, Anna; Ferraro, Ottavia E.; Saplioglu, Meltem; Otte, Dietmar; ,
Highlights: Cyclists are very often unaware of whether mandatory helmet law applies in their countries. The effect of mandatory helmet laws for cyclists is mediated by the knowledge of the law. Frequency of use of the bycycle helmet is related to the believe that a mandatory helmet law exists in a country. Abstract: To improve the safety of bicycle users, some countries have enacted, or considered enacting, mandatory helmet legislation. Of course, the enactment of such legislation in a country assumes that its citizens will be well-informed of it, and consequently, will use the helmet more frequently than before. However, in the survey described in this paper we found that many people are not aware of the legislation in force in their own country, or, even if they know, they may not necessarily behave as dictated by the law. Thus, the effects of mandatory helmet legislation may be somewhat different than desired or expected. Therefore, the goal of this paper is to ascertain the role of cyclists' knowledge of the law in their country as a mediator between the law and the actual use of the helmet. Respondents from seventeen countries participated in an international survey about cyclists' habits, and answered questions about helmet legislation, and frequency of helmet use. The results indicate that the main effect of mandatory helmet legislation on the frequency of use of the helmet is mediated by the perception that such a law exists in their country—even when in fact sometimes it does not exist.